Leadership Role in Improving Responsibility of Employee's Work in Scope of General Bureau of Government of Makassar - Amrin, Amrin; Sahabuddin, Chuduriah; Farida, Umi; Yusriadi, Yusriadi (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2020)
The role of leadership in improving the work responsibilities of employees in the scope of the Government of Makassar City, this study uses a qualitative method by using speakers from the leadership elements and several employees in the Government of Makassar City following the needs after being in the field. Analysis of the data used with the method of qualitative analysis is to compare the conditions in the area with standards or related theories so that conclusions can obtain. Results of the study show that the role of leadership in enhancing employee work responsibilities in the scope of Makassar City Government, in general, has gone well, namely using one-way relationships, the role of exemplary figures, supervisory/controlling functions, receiving information (relatively low) and in decision-making, but the part of leadership still needs to be increased, among others, using flexible two-way relationships, exemplary figures, making input of information as an organizational asset, transparent supervision, and decisions by optimally utilizing existing resources, decisions that contain dampers and opportunities or challenges.